DESAIN INOVASI ABAD KE 21: PENERAPAN MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI CAPCUT UNTUK MENCIPTAKAN PEMBELAJARAN YANG BERPIHAK PADA PESERTA DIDIK - Rina Rina; Juaidah Agustina (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to describe the application of animated video-based learning media using the CapCut application to create learning that supports students, namely by meeting the needs of students in class IX.10 of SMP Negeri 7 Palembang. This research meets the needs of students, especially in learning style and background. This research used a qualitative descriptive method, with research subjects 36 students in class IX.10. The data used in this research are, 1) the learning process using CapCut-based animated video learning media; 2) documents in the form of teaching modules; and 3) field notes obtained through the observation stage. The research results were carried out in several stages including: 1) conducting an initial assessment; 2) alignment of learning media; 3) creating teaching modules; 4) implementing learning; 5) reflection and evaluation. The results of reflection and evaluation show that students' enthusiasm and involvement in learning provides significant learning outcomes.